Hibernating Little Pocket Mice Show Few Seasonal Changes in Bone Properties. Issue 12 (23rd August 2017) - Pineda, Noellyn; Owen, Marjorie; Tucker, Claire; Wojda, Samantha; Kitchen, Stanley; Black, Hal; Donahue, Seth
ABSTRACT: Periods of disuse or physical inactivity increases bone porosity and decreases bone mineral density, resulting in a loss of bone mechanical competence in many animals. Although large hibernators like bears and marmots prevent bone loss during hibernation, despite long periods of physical inactivity, some small hibernators do lose bone during hibernation. Little pocket mice ( Perognathus longimembris ) remain underground during winter hibernation and undergo bouts of torpor and interbout arousals, but the torpor bout duration is shorter than other rodent hibernators. Additionally, little pocket mice may enter torpor during summer estivation. In this study, cortical and trabecular bone architectural, mineral, and mechanical properties were analyzed for femurs from little pocket mice captured during 8 different months (March to October) to determine seasonal effects on bone. There were no differences in any bone properties between the pre‐hibernation month of October and the post‐hibernation month of March, suggesting winter hibernation did not adversely affect bone properties. However, cortical area was higher in March than April, May, and June. Bone mechanical and osteocyte lacunar properties were not different between any months. Trabecular bone in the distal femoral epiphysis showed no changes between months. The distal femoral metaphyseal region showed higher trabecular spacing and lower trabecular number in May than August, otherwise, there were no differences in trabecular parameters. The few monthly differences in bone properties may be due to physical inactivity from periodic summer estivation or from the timing of birth and growth in spring and summer months. Anat Rec, 300:2175–2183, 2017. © 2017 Wiley Periodicals, Inc.